2020
DOI: 10.21203/rs.3.rs-16187/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Diabetic Retinopathy in Southwest Ethiopia: A facility-based case-control study

Abstract: Background: Diabetic Retinopathy is one of the serious complications patients’ diabetic patients suffer from. Little is known about which risk factors are associated with this complication. The aim of this study was therefore to identify determinants of Diabetic Retinopathy in Jimma University Medical Center. Methods: A facility-based case-control study was conducted. Cases were Diabetic patients with diabetic retinopathy and who were on follow up at the Jimma University Medical Center while controls were Diab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…An Ethiopian study of 311 patients with diabetes found that patients over the age of 60 were five times more likely to develop DR than those under 60, patients with poor adherence were three times more likely to develop DR than those who were adherent, and those with poor glycemic control were nine times more likely to develop DR than those with good glycemic control. 77 A study examining the adherence within the Atherosclerosis Risk in Communities Study, average participant age 75.4, found that 2119 participants, or about 40%, reported intermediate to poor compliance with their medication; of these participants, 75% of them said their non-adherence was due to poor memory. 78 Although these results look daunting, there were some positive takeaways from the study.…”
Section: Challenges For the Aging Populationmentioning
confidence: 99%
“…An Ethiopian study of 311 patients with diabetes found that patients over the age of 60 were five times more likely to develop DR than those under 60, patients with poor adherence were three times more likely to develop DR than those who were adherent, and those with poor glycemic control were nine times more likely to develop DR than those with good glycemic control. 77 A study examining the adherence within the Atherosclerosis Risk in Communities Study, average participant age 75.4, found that 2119 participants, or about 40%, reported intermediate to poor compliance with their medication; of these participants, 75% of them said their non-adherence was due to poor memory. 78 Although these results look daunting, there were some positive takeaways from the study.…”
Section: Challenges For the Aging Populationmentioning
confidence: 99%